Procedural Knowledge Instruments for Grade IV Elementary School - Widiastiningsih, Ni Luh Putu; Yudiana, Kadek; Widiana, I Wayan (Journal of Education Reseach and Evaluation, 2021)
The assessment process is not far from using the instrument as a tool in measurement. Some schools have not been able to use instruments to measure the ability of students' knowledge dimensions, one of which is procedural knowledge. Many factors influence such as the lack of teacher motivation in assessing students' procedural knowledge and there is no procedural knowledge instrument. This study aims to produce a valid and reliable procedural knowledge instrument on Theme 6 grade IV Elementary School. This research is development research conducted in ten stages, according to Brog & Gall, namely: Researching and collecting information, reading literature, making observations, and preparing reports on development needs; Planning prototype components to be developed, defining, formulating goals, determining the sequence of activities; Develop initial products; Conduct expert team test; Revise the initial based on the results of product trials; Conduct main field trials; Revise the product based on the results of field trials; Conduct operational field trials; Carry out final revision of field test products, and Conduct dissemination and implementation. The subjects in this study were 5 material expert lecturers, 22 students in small groups, and 141 students in large groups. In this study, data collection was carried out by interviews, observation, documentation, questionnaires, validity tests, reliability tests, discriminatory tests, level tests. The difficulty, and distractor analysis. From the results of this study we found that the prototype of the procedural knowledge instrument development was carried out in four stages, the procedural knowledge instrument was declared valid with the criteria pbi > rtable 5%, the procedural knowledge instrument was declared to have reliability (0.934). Based on the results of the study, it can be concluded that the procedural knowledge instrument for fourth-grade elementary school students has met the valid and reliable criteria.